2018
DOI: 10.1002/gps.4912
|View full text |Cite
|
Sign up to set email alerts
|

Change in quality of life after a multidisciplinary intervention for people with dementia: A cluster randomized controlled trial

Abstract: The stepwise intervention STA OP! affects the QUALIDEM domains in different ways: there was a lowering of Restless tense behavior in the short term, which reverted back to the initial level in the longer term, and a lowering of Social isolation in the longer term.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 42 publications
(85 reference statements)
0
8
0
Order By: Relevance
“…Indeed, a recent study found that an intervention which benefits challenging behavior, pain, and the use of medication, can also lead to improvements in domains of QoL (e.g. restless tense behavior and social isolation) in NH residents with advanced dementia [60].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, a recent study found that an intervention which benefits challenging behavior, pain, and the use of medication, can also lead to improvements in domains of QoL (e.g. restless tense behavior and social isolation) in NH residents with advanced dementia [60].…”
Section: Discussionmentioning
confidence: 99%
“…Actually, some systematic reviews demonstrated that multicomponent interventions were more effective than single activities in improving general well-being of both persons with dementia and their caregivers (70, 175), and in hospitalized older adults with cognitive impairment (176, 177).…”
Section: Multicomponent and Multidimensional Strategiesmentioning
confidence: 99%
“…This study aimed to include 95 LTCF residents aged ≥ 65 years, with (advanced) dementia stage 5, 6, or 7 according to the Reisberg Global Deterioration Scale [ 24 ] and a moderate to low QoL, total score ≤ 70 on QUALIDEM-6-Domain total score (QUALIDEM-6D), independent of having pain. This cut-off point was derived from the median of the QUALIDEM-6D scores found in a previous Dutch study involving persons with dementia living in LTCFs [ 25 , 26 ].…”
Section: Methodsmentioning
confidence: 99%